Proanthocyanidin monomers and cyanidin 3-o-glucoside accumulation in blood-flesh peach (Prunus persica (l.) Batsch) fruit - Yan, Juan; Cai, Zhi-xiang; Shen, Zhi-jun; Ma, Rui-juan; Yu, Ming-liang (Archives of Biological Sciences, 2017)
To better understand the characteristics and mechanisms of proanthocyanidin monomers and anthocyanin synthesis in blood-flesh peach (Prunus persica (L.) Batsch), the accumulation of catechin, epicatechin and cyanidin 3-O-glucoside was determined, and the expression patterns of structural genes associated with biosynthesis of those compounds were investigated in the blood-flesh peach fruit of cultivar “Dahongpao” during fruit development. Our results show that catechin concentration remained low and comparatively stable throughout fruit development. The concentration of epicatechin remained low at the early stages of fruit development and rapidly accumulated during ripening. Cyanidin 3-O-glucoside was not detected in the early stages. Epicatechin started to rapidly accumulate during the ripening period, reaching a maximum at the mature stage. The expressions of the early and common genes, phenylalanine ammonia-lyase and chalcone isomerase, were less associated with proanthocyanidin monomers and cyanidin 3-O-glucoside accumulation. The expression of other flavonoid ‘early’ biosynthetic genes, including chalcone synthase (CHS), flavanone 3-hydroxylase, dihydroflavonol 4-reductase (DFR) and leucoanthocyanidin dioxygenase (LDOX), were partly associated with proanthocyanidin monomers and cyanidin 3-O-glucoside levels, with expression quantities peaking synchronously at the mature stage. Leucoanthocyanidin reductase and anthocyanidin reductase, which were the key genes for proanthocyanidin monomer synthesis, correlated during fruit development with catechin and epicatechin accumulation respectively; UDP-glucose: ﬂavonoid 3-O-glucosyltransferase (UGFT), the key gene for anthocyanin synthesis, was correlated with cyanidin 3-O-glucoside levels. The synchronous accumulation of epicatechin and cyanidin 3-O-glucoside in blood-flesh peach could not be explained by the current theory of competitive distribution mechanism of common substrate. https://doi.org/10.2298/ABS161212006Y Received: December 12, 2016; Revised: January 12, 2017; Accepted: February 7, 2017; Published online: March 2, 2017 How to cite this article: Yan J, Cai Z, Shen Z, Ma R, Yu M. Proanthocyanidin monomers and cyanidin 3-O-glucoside accumulation in blood-flesh peach (Prunus persica (L.) Batsch) fruit. Arch Biol Sci. 2017;69(4):611-7.